Kebijakan Pengelolaan Dana Pinjaman Penerima Kartu Tanda Perserta KSP KUD Pilar Pada Plasma PT TKA di Nagari Alahan Nan Tigo, Kecamatan Asam Jujuhan, Kabupaten Dharmasraya - Kasramika, Kasramika; Juliardi, Budi; Rudagi, Reindy (Darul Yasin Al Sys, 2023)
Plasma is community land managed by PT TKA and cooperatives. This land is carried out in a system of cooperation by the community with PT TKA and the cooperative. Therefore, the community benefits from plasma cards. However, plasma cards are only obtained for people who are recorded in 2001, while those who do not have plasma cards cannot receive plasma money every month and are not can borrow directly from the cooperative, this plasma card can be inherited and can also be traded for people who can afford it, the condition is that the community got this plasma in 2001, namely that the community has a family card The purpose of this study was to determine the policy of managing loan funds for plasma card recipients in Nagari Alahan Nan Tigo, Asam Jujuhan District, Dharmasraya Regency. The theory used in this study is the theory of functional structure put forward by Talcott Parson. This research was conducted in Nagari Alahan Nan Tigo, Asam Jujuhan District, Dharmasraya Regency. This study used a qualitative research method with a descriptive research type. Withdrawal of informants from cooperative heads, community leaders and borrowers. the data collection in this study begins with observation, interviews, and document study. carried out with several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that there were several policies for managing loan funds for plasma card recipients in Nagari Alahan Nan Tigo, Asam Jujuhan District, Dharmasraya Regency, 1) PT TKA policies in managing loan funds for plasma card recipients. Rp. 10,000 agreed upon by the community, the community will receive external plasma from the total deductions of Rp. 850,000. 2) The benefits obtained by plasma card holders from loan funds are helping the community's economy, helping children's education costs, people lacking capital in their business can pawn their plasma cards to the cooperative office, plasma cards can also be traded for people who can afford them and plasma cards these can also be inherited.